VADIVELU DIALOGUES AN ANYONE'S COLLOQUIALISM AND IDIOLECT - et. al., Broskhan. P, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of humor can be understood by looking at the meaning of the Tamil proverb, "If you smile, you will get rid of the disease". The most interesting in cinema can also be the most desirable and always-seen scene comedy. Everyone from the youngest to the oldest loves comedy. Any idea is easily reached when told through humor. As far as Tamil cinema is concerned, a lot of comedians make people laugh and think. Vadivelu in particular has a very important place in the personality. Vadivelu may be a reaction of the common people. This study explores the linguistics that Vadivelu used in the verse he used in his comedy scenes. Tamil languages use a wide variety of Colloquialism and Idiolect. We use many language strategies in our daily lives. For example, proverbs and stories are popular among the Tamil people. Vadivelu used this linguistic technique extensively in films. Five films released in different eras were Manathai Thirudi Vittai(2001), Arya(2007), Chandramuki(2005), Pokkiri(2007) and Talanagaram (2006). The comedy of these films is still widely talked about among the people today as these films were released a while back. The reason for examining these films may be the character of Vadivelu in these films and the verses used in them. We seek to examine how Vadivelu's verses are inspired and used in the normal life of the people. The purpose of this study is to determine how characterization in language takes place in the individual and the basic biology of a group. And how this linguistic characteristic takes place in films. In particular we explore the connection between the success of Vadivelu’s comedy scenes and social use.